Maternal Alexithymic Traits Are Related to Lower Maternal Sensitivity and Higher Hostility in Maternal Caregiving Behavior—The FinnBrain Birth Cohort Study - Ahrnberg, Hanna; Korja, Riikka; Scheinin, Noora M.; Nolvi, Saara; Kataja, Eeva-Leena; Kajanoja, Jani; Hakanen, Hetti; Karlsson, Linnea; Karlsson, Hasse; Karukivi, Max (Frontiers in Psychology, 2021)
Background The quality of parental caregiving behavior with their child plays a key role in optimal mother-infant interaction and in supporting child adaptive development. Sensitive caregiving behavior, in turn, requires the ability to identify and understand emotions. Maternal alexithymia, with difficulties in identifying and describing feelings or emotions, as well as a concrete way of thinking, could potentially complicate the quality of caregiving. In this study, we aim to explore the possible association between maternal alexithymic traits and the quality of maternal caregiving behavior. Methods The study sample consisted of 158 mother-infant dyads within the FinnBrain Birth Cohort Study population with an available report of maternal alexithymic traits at six months postpartum and observational data on maternal caregiving behavior at eight months postpartum. Alexithymia was measured using the 20-item Toronto Alexithymia Scale (TAS-20) including three alexithymia dimensions – Difficulty Identifying Feelings (DIF), Difficulty Describing Feelings (DDF), and Externally Oriented Thinking (EOT). Maternal caregiving behavior was assessed using the Emotional Availability Scale (EAS) and in this study, all four parent dimensions (Sensitivity, Structuring, Non-intrusiveness and Non-hostility) were included. Maternal depressive and anxiety symptoms at six months postpartum were controlled for as potential confounders. In addition, background factors of mother’s age and gestational weeks at the time of child birth, maternal educational level, monthly income and parity, as well as relationship status and the gender of the baby were assessed. Results Maternal TAS-20 total score correlated negatively with Sensitivity (r=-0.169, p=0.034) and with Non-intrusiveness (r=-0.182, p=0.022). In addition, maternal DDF correlated negatively with Sensitivity (r=-0.168, p=0.035) and EOT with Non-hostility (r=-0.159, p=0.047). Furthermore, in regression analyses with controlling for the associated background factors, maternal total score of alexithymic traits (p=0.034, η2p=0.029) and higher DDF (p=0.044, η2p=0.026) remained significantly associated with lower Sensitivity and higher EOT remained significantly associated with lower Non-hostility (p=0.030, η2p=0.030). Conclusions In this explorative study we found preliminary evidence for the hypothesis that higher maternal alexithymic traits associate with lower maternal sensitivity and more hostile maternal caregiving behavior. Further studies are needed to explore these hypotheses and to investigate their possible implications for child development.